Effective Factor on Delivery and on Choosing its Type in IRAN: A Phenomenological Study - Leili Mosalanejad (International Journal of Public Health Science (IJPHS), 2013)
Different factors such as economical, social, and cultural may have a considerable role in choosing the type of delivery. Considering the importance of women’s idea and decision in choosing the type of delivery, this study was done by purposing on explaining women’s experiences in delivery and choosing its type in a qualitative study.This was a descriptive qualitative study (phenomenology approach)  that was done by purposeful sampling on non-nulliparous pregnant women who were in the third trimester of pregnancy referred to Jahrom maternity clinics . The purposeful sampling was used for studying urban and rural pregnant women in six focus groupsincluding seven pregnant women in each   that data gathering continued to the point of data saturation and data were analyzed using content analysis. From 98 dismissed codes, two main teams and nine sub teams emerged that included their perception delivery and their cultural socioeconomic level. There were many factors affecting the selection of the type of delivery that some of them are the result of the lack of accurate information, poor education and lack of comprehensive rational and decisions regarding women’s healthcare. Therefore it is necessary to adapt appropriate strategies to improve children and mother’s health. DOI: http://dx.doi.org/10.11591/ijphs.v2i4.3882